Adaptive robust control of oxygen excess ratio for PEMFC system based on type-2 fuzzy logic system - Zhang, H.K.; Wang, Y.F.; Wang, D.H.; Wang, Y.L. (Information sciences, 2020)
The Proton Exchange Membrane Fuel Cell (PEMFC) air supply system takes on the characteristics of external disturbances and uncertain parameters, which is difficult to achieve accurate modeling and stability control. In this paper, an adaptive robust controller based on type-2 fuzzy logic systems (T2-FLS) is proposed to control the oxygen excess ratio (OER) of PEMFC air supply system. The controller does not need the unmodeled dynamics, which can be approximated by adaptive T2-FLS whose adaptive parameters are derived based on Lyapunov theory. The stability analysis shows that the system tracking error is uniform ultimate bounded. Finally, the practicability and feasibility of controller are validated by numerical simulation and Hardware-In-Loop (HIL) experiment.